Effects of Diabetes Self-Care Calendar on Self-Care Behavior, Knowledge, and HbA1c among Type 2 Diabetes Mellitus Patients: A Randomized Controlled Trial - Sugiharto Sugiharto; Hsu Yu-Yun (Indonesian Contemporary Nursing Journal (ICON Journal), 2026)
Aims: To examine the effects of a diabetes self-care calendar on self-care activities, diabetes knowledge, and glycemic control in individuals with type 2 Diabetes Mellitus.  Methods: This study used a randomized controlled trial design. This study employed a proportionate random cluster selection. The participants were blindly divided into intervention and control groups. The study was conducted at three community health centers in the region. The intervention group was provided with a Diabetes Self-Care Calendar (DSCC). The control group received conventional care. The summary of diabetes self-care activities and the diabetes knowledge questionnaire (Indonesian version) were used to assess the participants’ self-care performance and knowledge. The Infopia Clover A1c AnalyserTM was used to measure HbA1c levels. These variables were measured twice, at two months and four months after the intervention. A repeated-measures ANOVA and t-test were used to analyze the hypotheses. Results: A total of 126 patients with type 2 diabetes mellitus were enrolled in this study, which were equally divided into an intervention group and a control group. The results showed that the DSCC significantly (p<0.001) increased the diet, physical activity, self-monitoring of blood glucose, foot care, and medication adherence. The diabetes knowledge and HbA1c levels in the intervention group were significantly greater than those in the control group (p<0.001 and p=0.001), respectively. Conclusion: The diabetes self-care calendar enhances self-care activity adherence, knowledge, and HbA1c. As a reminder, the calendar obeys the pillars of diabetes self-care; it is an age-friendly and family empowered reminder and is usable.